MAKING OF INSTRUMENT NON-TECHNICAL COMPETENCY ASSESMENT BASED ON BEHAVIOR INTERVIEW (BEHAVIOR BASED INTERVIEW) IN PT"X" - Prasetya, Yudhi; Effendy, Nurlaila; Halim, L. Verina (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2013)
The phenomenon of competition among industry companies is notsomething new. PT. âXâ is one of the food industry are trying to applyhuman resource management for the company to remain competitive withother similar industries. PT. âXâ hope to have competent workers in thefield that the worker will be able to contribute in improving operationalperformance of the companys. In creating a competent worker takes theright steps to develop existing their competencies. Measurement withbehavior-based interview (BBI) is one way that can be recommended to thecompany in order to identify the competencies of workers. Method of datacollection in this research using interviews, observations, and discussionswith management. The results is an overview of the process to making ofguidelines for interview BBI especially non-technical competencies. Ingeneral, the things that need to be prepared is to understand the competencydictionary, how to reduce the question of the competence of the companyscompetency dictionary, and the need for skills such as probing interviews,parafrashing, and others.